On Moral Development in Education through Experience: Natural and Free Human being in Rousseau - Savruk, Demet; Kenan, Seyfi (ANI PUBLISHING, 2021)
The universal problems faced by humankind from past to present inevitably drawing attention to an ethical context of and the function of education. These problems, which societies face despite all the advances, lead us to discuss what can be done regarding curriculum studies. These discussions were brought to the agenda through the questions and conceptualizations based on Rousseau's First Discourse (1749) and Emile (1762), and answers were sought in today's context. Rousseau's major works constitute the study group of this research conducted with the conceptual analysis method. Despite the general acceptance of the fundamental place of ethical arguments in the views affecting the philosophical foundations of the curriculum, the abstraction of it in practice leads to a mechanical understanding of education. Needs for comprehension of experience-based education and the creation of new paradigms with ethical grounds that formulates according to local dynamics become more apparent and critical amidst the challenges that our world faces.
Keywords: J. J. Rousseau; experience; human nature; freedom; ethics; Education & Educational Research